(untitled) (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
The teaching of grammar and vocabulary is a complex but crucial process in the course of an educationaland epistemological programmeforlearning any language, especially English. It is all mandatory fora teacher of English to teach vocabulary and grammar so that the learner can develop the four basic skills of learning a language. In every teaching strategy, a method followed by a theory, objectives determination (general and specific), syllabus designing, curriculum scheduling, checklist assembling, material selecting, and lesson planning are marked as the mandatory steps to be taken by a teacher of English. In case of methods, generally four types of method i.e. Grammar Translation method, Directmethod, Audio-lingual method and Communicative Language Teaching method can be specified. Further, in case of teaching vocabulary, diverse methods particularly- keyword method, word map,restructuring reading materials, root analysis and so on can also be marked as necessary. While we come across syllabus designing, we find: Grammatical syllabus, Structural syllabus, Situational syllabus and Notional-functional syllabus. In case of materials we have textbooks, workbooks, reference books, teachers manual, supplementary materials, remedial materials and so on. After selection of materials, the selection of gradation comes including linear and cyclic gradation. The checklist is a kind of manual or work-plan provided by the teacher to the students. As a whole, the checklist includes daily programme of topics selected in specific to be taught in a lecture or several lectures whereas a lesson plan is a detail discussion of the topic with the division of time scheduling for each and every class.